Fe-TiO2 Nanoparticles Synthesized by Green Chemistry for Potential Application in Waste Water Photocatalytic Treatment - Ricardo A. Solano; Adriana P. Herrera; David Maestre; Ana Cremades (Journal of Nanotechnology)
Anatase TiO2 nanoparticles doped with iron ions have been synthesized via the green chemistry method using aqueous extract of lemongrass (Cymbopogon citratus) obtained from Soxhlet extraction and doped by wet impregnation. The TiO2 anatase phase has been doped with Fe3+ (0.05, 0.075, and 0.1 Fe3+ : Ti molar ratio) at 550°C and 350°C, respectively. The scanning electron microscopy with energy-dispersive X-ray (SEM-EDS) shows nanoparticle clusters and efficiencies of impregnations between 66.5 and 58.4% depending on the theoretical dopant amount. The electron transmission microscopy (TEM) reveals final particle sizes ranging between 7 and 26 nm depending on the presence or not of the dopant. The cathodoluminescence (CL) and photoluminescence (PL) studies of the doped and undoped nanoparticles show a luminescence signal attributed to surface oxygen vacancies (visible CL emission 380–700 nm and PL emission 350–800 nm); additionally, a decrease in emission intensity is observed due the inhibition of the recombination of the photogenerated electron-holes pairs; moreover, nanopowders were analyzed by UV-Vis spectrophotometry of diffuse reflectance, and the absorption edge of the Fe-TiO2 in comparison to undoped TiO2 is extended greatly toward the visible light. The six bands (A1g + 2B1g + 3Eg) found by Raman spectroscopy and the x-ray diffraction pattern (XRD) confirm that synthesized TiO2 is only anatase phase, which is commonly used as a catalyst in waste water treatment, specifically in heterogeneous photocatalytic processes.